ظاهرة السلب في خصائص ابن جني - خشيبة, إيمان; بوضبية, سامية; كرطي, شيماء (University of Eloued جامعة الوادي, 2024)
تناولت مذكرتنا موضوعا هاما يتناول ظاهرة لغوية نادرة وقليلة التطرق تسمى" ظاهرة السلب" عند الدارسين العرب عموما وابن جني خصوصا، وليقسم بذلك موضوعنا إلى قسمين شق نظري: استقرأنا فيه ظاهرة السلب، وشق تطبيقي: خصصناه لابن جني وخصائصه بذكر مفهومه وأنواعه، وقد اتبعنا في ذلك المنهج الوصفي لوصف ظاهرة السلب بكل تفاصيلها، وتوصلنا إلى أن ابن جني قد تفرد على غرار علماء العربية في تخصيصه بابا كاملا لهذه الظاهرة وبيان تمفصلاتها، وبيان حقيقتها في المجال الصرفي ووظيفتها بالوقف على أهم دلالاتها. Our memorandum addressed an important topic that discusses a rare linguistic phenomenon that is rarely discussed، known as "the phenomenon of negation" among Arabic scholars in general and Ibn Jinni in particular. Accordingly، our subject was divided into two theoretical and applied sections. In the theoretical section، we examined the phenomenon of negation، while in the applied section، we focused on Ibn Jinni and his characteristics، mentioning the concept of negation and its types. We followed a descriptive approach to describe the phenomenon of negation in all its details، and we concluded that Ibn Jinni distinguished himself، like other Arabic scholars، by dedicating an entire section to this phenomenon and explaining its intricacies، its true nature in the field of morphology، and its function in understanding its important implications.
دراسة صرفية دلالية -
لسانيات عامة
Keywords: ظاهرة السلب، ابن جني، كتاب الخصائص; negation phenomenon، Ibn Jinni، Book of Characteristics.